2021
DOI: 10.3389/fmicb.2021.733385
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Induced by the N-Terminus of the Classic Swine Fever Virus Nonstructural Protein 5A Protein Promotes Viral Replication

Abstract: Although classic swine fever virus (CSFV) infection has been reported to induce autophagy, the specific induced mechanism remains unrevealed. Nonstructural protein 5A (NS5A) of CSFV is a multiphosphorylated protein with multiple functions to regulate viral replication and the host cell immune responses. Herein, we demonstrated that CSFV NS5A could induce cellular autophagy and promote viral replication. In the current study, we showed that NS5A expression significantly increased the levels of autophagy-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Jefferson et al demonstrated that pestivirus N pro curbed endogenous mitochondrial apoptosis by inhibiting the activation of the IRF3-dependent pro-apoptotic protein Bcl2-Associated X (BAX), indicating that mitochondria and peroxisomes may be new sites for N pro to regulate IRF3 (Jefferson et al, 2014). Additionally, pestivirus infection induced autophagy to promote virus replication (Pei et al, 2014;Oguejiofor et al, 2019;Zhang et al, 2021). Explored the mechanism and found that CSFV-mediated autophagy restrained the expression of IFN-I.…”
Section: Other Viral Proteins Inhibit Ifn Productionmentioning
confidence: 99%
“…Jefferson et al demonstrated that pestivirus N pro curbed endogenous mitochondrial apoptosis by inhibiting the activation of the IRF3-dependent pro-apoptotic protein Bcl2-Associated X (BAX), indicating that mitochondria and peroxisomes may be new sites for N pro to regulate IRF3 (Jefferson et al, 2014). Additionally, pestivirus infection induced autophagy to promote virus replication (Pei et al, 2014;Oguejiofor et al, 2019;Zhang et al, 2021). Explored the mechanism and found that CSFV-mediated autophagy restrained the expression of IFN-I.…”
Section: Other Viral Proteins Inhibit Ifn Productionmentioning
confidence: 99%
“…For example, by binding to LC3, the NS5A protein increases the expression of ATGs and activates complete autophagy, thus promoting virus replication. Notably, the phosphorylation of NS5A at 81 and 92 aa within its Nterminal region is essential for activating autophagy (Zhang et al, 2021a). Further, NS3 directly binds to lactate dehydrogenase B (LDHB), a key glycolysis metabolic enzyme that catalyzes the transformation of pyruvate and lactic acid in the anaerobic glycolysis pathway and inhibits LDHB, activating mitochondrial autophagy (Fan et al, 2021).…”
Section: Increases Btv Replicationmentioning
confidence: 99%
“…For instance, a few studies indicate that NS5A protein interacts with eukaryotic translation initiation factor 3 subunit E (eIF3E), ras-related protein 18 (Rab-18), glucose-regulated protein 78 (GRP78), heat shock protein 70 (Hsp70) and so on to facilitate viral replication (10)(11)(12)(13). Recent studies revealed that NS5A induces autophagy to enhance replication of CSFV (14,15). It has also been shown that CSFV NS5A protein could inhibit the secretion of inflammatory cytokines by suppressing the NF-kB pathway (16).…”
Section: Introductionmentioning
confidence: 99%